PERANCANGAN SISTEM INFORMASI PENGAJUAN BARANG PADA AMIK AKMI BATURAJA - Satria Novari (Jurnal Informatika, 2013)
The goods submission is a process which is undertaken by a staff or an employee to obtain the needed goods. The process of the goods submission at AMIK AKMI Baturaja still use manual system, so it makes some problems just as there are the submission documents are not archived well and if the an employee will propose and the staff of domesticity department is not in place, the goods submission have to be postponed at a later time. This will hinder the process of submission goods. The method of this research uses iterative method, it means that every builds a module, the process undertaken is a design and a development, a testing and an implementation. The result of this research is a system which is able to help the employees or the staff of the domesticity department in managing the goods submission.Keywords: information system, the filling goods, iterative model